Developing Self-Study Competence of Students through Experiential Activities in the Digital Environment - Thanh Tu Ngo; Nhung Kim Thi Vu; Thanh Chi Phan (Indonesian Journal Of Educational Research and Review, 2022)
Digital Technologies including Big Data, Artificial Intelligence (AI), and Data Mining have created a revolution in education: switching from traditional teaching method to self-teaching method, which can maximize the self-study competence of learners to meet changes in digital technologies. The research aims to develop methods of for organizing experiential teaching in order to maximize the self-learning abilities of students in the digital environment and meet the development of advanced science and technology. This research used mixed which qualitative and quantitative methods to analysis and assessment. This research focuses on high-level experiential learning which an experience is: group discussion, experimentation & practice for certain subjects, namely the embedded system. The result of this research has presented the scientific basis for developing self-study competence through experiential activities in the digital environment and proposed two strategies to organize experiential activities in the digital environment to develop students' self-efficacy.